Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.05.02.22274561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Artificial Intelligence for context-aware surgical guidance in complex robot-assisted oncological procedures: An exploratory feasibility study

Abstract: Background: Complex oncological procedures pose various surgical challenges including dissection in distinct tissue planes and preservation of vulnerable anatomical structures throughout different surgical phases. In rectal surgery, a violation of dissection planes increases the risk of local recurrence and autonomous nerve damage resulting in incontinence and sexual dysfunction. While deep learning-based identification of target structures has been described in basic laparoscopic procedures, feasibility of ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…On the one hand, it can be used as a source of further image material in combination with other, already existing datasets. On the other hand, it can be used to create organ detection algorithms working either with weak labels or with semantic segmentation masks, for example as a basis for further development of assistance applications 17 . Proposed training-validation-test splits as well as results of detailed segmentation studies are reported in a separate publication 18 .…”
Section: Usage Notesmentioning
confidence: 99%
“…On the one hand, it can be used as a source of further image material in combination with other, already existing datasets. On the other hand, it can be used to create organ detection algorithms working either with weak labels or with semantic segmentation masks, for example as a basis for further development of assistance applications 17 . Proposed training-validation-test splits as well as results of detailed segmentation studies are reported in a separate publication 18 .…”
Section: Usage Notesmentioning
confidence: 99%
“…Given that incomplete TME is directly associated with local tumor recurrence and reduced overall survival, TME represents a crucial step in rectal cancer treatment [ 51 , 52 , 53 ]. In a recent study [ 54 ], supervised machine learning models were used to identify various anatomical structures throughout different phases of robot-assisted rectal resection and to recognize resection planes during TME ( Figure 2 ). In this monocentric study, detections were most reliable for larger anatomical structures such as Gerota’s fascia or the mesocolon with mean F1 scores of 0.78 and 0.71, respectively, the mean F1 score for detection of the dissection plane (“angel’s hair”) during TME was 0.32, while the exact dissection line could be predicted in few images (mean F1 score: 0.05).…”
Section: State-of-the-art Of the Intraoperative Application Of Aimentioning
confidence: 99%
“…The same principle can be applied to oncologic resections. For example, models implemented by two independent groups have attempted to use DL, CNN, and segmentation to identify the total mesorectal excision (TME) plane of dissection during rectal cancer resections (23,24). This is particularly important given the difficulty of staying in the correct plane of dissection during rectal surgery.…”
Section: Intraoperative Applications Of Computer Vision In Surgerymentioning
confidence: 99%